2021
DOI: 10.1108/ajim-03-2021-0080
|View full text |Cite
|
Sign up to set email alerts
|

Examining the factors influencing college students’ continuance intention to use short-form video APP

Abstract: PurposeThe purpose of this study is to explore the effects of recommendation algorithm, product reputation, new product novelty, privacy concern and privacy protection behavior on users’ satisfaction and continuance intention to use short-form video application (APP).Design/methodology/approachBased on the existing theories, the research model of this study was developed and 445 valid data were collected through a questionnaire survey. The partial least squares structural equation modeling (PLS-SEM) was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 71 publications
1
17
0
Order By: Relevance
“…SVAs enable users to create and share videos that last several seconds to a few minutes [ 4 ]. The easy-to-use interfaces, fascinating content, novel gameplay, personalized recommendation, and immersive experiences afforded by SVAs may tempt users to consume short-form videos excessively and become addicted [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…SVAs enable users to create and share videos that last several seconds to a few minutes [ 4 ]. The easy-to-use interfaces, fascinating content, novel gameplay, personalized recommendation, and immersive experiences afforded by SVAs may tempt users to consume short-form videos excessively and become addicted [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Noticeably, prior empirical studies have demonstrated that individuals in stressful states used smartphones or the internet more often [ 38 , 41 , 42 ], and such usage relieved their negative feelings from stressful life situations [ 32 , 43 , 44 ]. Given that watching short-form videos can help users relax [ 4 , 6 ], middle-aged adults are likely to rely on SVAs to alleviate stress. Hence, the more under stress a middle-aged person is, the more likely it is that they are.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that contents, forms, and the mode of human-computer interaction constitute a typical scenario of technology use, we draw upon prior research (Sundar and Limperos, 2013 ; Zhang et al, 2019 ; Zhao, 2021 ) and propose three affordances of SVAs that induce users to consume contents (i.e., recommendation algorithm), utilize various forms to edit (i.e., multimodality), and interact with the interface in specific ways (i.e., low-cost interaction). Recommendation algorithm is widely used in the design of various mobile applications, through which the platforms tailor information and services according to users' preferences, thereby increasing user satisfaction (Moon et al, 2014 ; Mou et al, 2021 ). In reference to previous research (Zhang et al, 2019 ), we consider recommendation algorithm a content-related affordance and define it as the perceived potential of SVA platforms to provide users with customized contents and services based on their preferences.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…The commercialization of short video applications has attracted more companies to enter this field to compete for markets and users in order to reap the dividends of the technological revolution, and competition has led to the emergence of similar IT systems and equipment products in the market, which have sprung up in the lives of the public ( Hayes et al, 2020 ). However, while the boom in short video applications has enriched the lives of the public, it has also intensified the level of commercialized competition ( Mou et al, 2021 ). More seriously, the more prominent problem of short video applications homogeneity has in turn further intensified the fierce competition in short video applications ( Zhao and Jie, 2020 ).…”
Section: Introductionmentioning
confidence: 99%